2022
DOI: 10.1371/journal.pone.0263818
|View full text |Cite
|
Sign up to set email alerts
|

The association of health insurance and race with treatment and survival in patients with metastatic colorectal cancer

Abstract: Background Black patients and underinsured patients with colorectal cancer (CRC) present with more advanced disease and experience worse outcomes. The study aim was to evaluate the interaction of health insurance status and race with treatment and survival in metastatic CRC. Materials and methods Patients diagnosed with metastatic CRC within NCDB from 2006–2016 were included. Primary outcomes included receipt of chemotherapy and 3-year all-cause mortality. Multivariable logistic regression and Cox-regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Patients identified as Black were associated with less desirable/worse outcomes in this and other studies 42,44,56 . Consistent with prior studies, patients with non-private insurances were associated with less desirable/worse outcomes 41,43 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Patients identified as Black were associated with less desirable/worse outcomes in this and other studies 42,44,56 . Consistent with prior studies, patients with non-private insurances were associated with less desirable/worse outcomes 41,43 .…”
Section: Discussionsupporting
confidence: 85%
“…Including potentially modifiable clinical variables in the lowest-/highest-risk scenarios showed stark differences in DOOR and TO probabilities, demonstrating how presentation acuity might result in care disparities. Other studies typically limit social risk factors to a single variable 11,41,42 or lack important variables such as neighborhood deprivation, 43,44 which underestimates the risk in vulnerable populations. Relationships between race/ethnicity, insurance type and neighborhood deprivation are complex, interdependent, and confounded.…”
Section: Discussionmentioning
confidence: 99%
“…4 Studies have shown that uninsured or underinsured patients are less likely to receive appropriate cancer treatment and more likely to have increased morbidity and mortality. [5][6][7] Many existing CAT epidemiology studies have been conducted in Caucasian European countries with universal healthcare systems. [8][9][10] Within the US, CAT studies have either relied on cancer registry-linked discharge claim databases without outpatient follow-up or private insurance claims databases without mortality data.…”
Section: Introductionmentioning
confidence: 99%
“…Recent US Census Data have shown that approximately 1 in 10 remains uninsured 4 . Studies have shown that uninsured or under‐insured patients are less likely to receive appropriate cancer treatment and more likely to have increased morbidity and mortality 5–7 . Many existing CAT epidemiology studies have been conducted in Caucasian European countries with universal healthcare systems 8–10 .…”
Section: Introductionmentioning
confidence: 99%
“…As well, this reflects a more judicious choice of therapy in patients who may draw limited benefits, given how costly these treatments are and the uncertainties surrounding the cost-effectiveness of these therapies . Second, while we anticipated that, compared with White patients, historically marginalized patient populations would have lower odds of receiving targeted therapies, especially in light of extensive prior documentation of higher mortality among Black patients with mCRC, our findings unexpectedly showed that Black patients had higher odds of receiving such treatment. We note, however, that because of absent data on tumor sidedness, we were unable to determine the appropriateness of the treatment received with respect to EGFR inhibitors.…”
Section: Discussionmentioning
confidence: 79%